Behavioral Assessment of the Negative Emotion Aspect of Distress Tolerance: Tolerance to Emotional Images. (April 2019) - Veilleux, Jennifer C.; Pollert, Garrett A.; Zielinski, Melissa J.; Shaver, Jennifer A.; Hill, Morgan A.
The current behavioral tasks assessing distress tolerance measure tolerance to frustration and tolerance to physical discomfort, but do not explicitly assess tolerance to negative emotion. We closely evaluated the conceptual distinctions between current behavioral tasks and self-report tasks assessing distress tolerance, and then developed a new behavioral distress tolerance task called the Emotional Image Tolerance (EIT) task. The EIT task retains elements of existing behavioral tasks (e.g., indices of persistence) while augmenting the reliability and content sufficiency of existing measures by including multiple trials, including a variety of negative affect stimuli, and separating overall task persistence from task persistence after onset of distress. In a series of three studies, we found that the EIT correlated with extant behavioral measures of distress tolerance, the computerized mirror-tracing task and a physical cold pressor task. Across all of the studies, we also evaluated whether the EIT correlated with self-report measures of distress tolerance and measures of psychopathology (e.g., depression, anxiety, and binge eating). Implications for the refinement of the distress tolerance construct are discussed.